Overview of laser-driven generation of electron–positron beams. (August 2015) - Sarri, G.; Dieckmann, M. E.; Kourakis, I.; Di Piazza, A.; Reville, B.; Keitel, C. H.; Zepf, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Electron–positron (e–p) plasmas are widely thought to be emitted, in the form of ultra-relativistic winds or collimated jets, by some of the most energetic or powerful objects in the Universe, such as black-holes, pulsars, and quasars. These phenomena represent an unmatched astrophysical laboratory to test physics at its limit and, given their immense distance from Earth (some even farther than several billion light years), they also provide a unique window on the very early stages of our Universe. However, due to such gigantic distances, their properties are only inferred from the indirect interpretation of their radiative signatures and from matching numerical models: their generation mechanism and dynamics still pose complicated enigmas to the scientific community. Small-scale reproductions in the laboratory would represent a fundamental step towards a deeper understanding of this exotic state of matter. Here we present recent experimental results concerning the laser-driven production of ultra-relativistic e–p beams. In particular, we focus on the possibility of generating beams that present charge neutrality and that allow for collective effects in their dynamics, necessary ingredients for the testing pair-plasma physics in the laboratory. A brief discussion of the analytical and numerical modelling of the dynamics of these plasmas is also presented in order to provide a summary of the novel plasma physics that can be accessed with these objects. Finally, general considerations on the scalability of laboratory plasmas up to astrophysical scenarios are given.